KEDUDUKAN MAZHAB SYAFI'I DALAM AMALAN PEMBAHAGIAN PUSAKA DAN WASIAT ISLAM DI MALAYSIA - Sulong, Jasni (Jurnal Syariah, 2019)
Mazhab Syafi‘i is a school of law which dominated Malaysia since the coming of Islam in Malay Archipelago. The teaching of Syafi‘i’s school of law was disseminated by the scholars through teachings, writings, judgments, personal opinions and even promulgated it in the statute of law. This situation led the teaching of the school was absorbed by the Muslims in most part of the country especially in their religious practice. Focusing in the law of inheritance and bequeath, the teaching of the Syafi‘i’s doctrine in this field was spreading exclusively and it was reflected from many cases and fatwas’. The practice was very firm among the people till any rule was based on Syafi‘i’s teaching. The kathi refused to refer to any other school of law even though there is more wisdom such as in the case there is solely an heir of dhu arham. Thus, this paper is intend to discuss of further development in the acceptance of Syafi‘i’s school in Malaysia as well as the practice of talfiq wa takhayyur (eclectic choice) of madhhab. The intention is to portray the real situation in getting the reference in the administration of Islamic law in Malaysia nowadays with special reference to the applications of Syafi‘i’s school of law in inheritance and wills.